Googling Location for Operating Base of Mobile Stroke Unit in Metropolitan Sydney - Phan, Thanh G.; Beare, Richard; Srikanth, Velandai; Ma, Henry (Frontiers in Neurology, 2019)
Background and Purpose: The recent advances in stroke therapy has placed focus of delivering care within the first hour after stroke onset (golden hour), principally through the use of Mobile Stroke Unit (MSU) to bring the hospital to the patient. The aim of this project is to search the location of MSU hub in Sydney, Australia, optimizing for catchment, transport to nearest thrombolysis capable hospital and population at risk. Methods: Traveling time was performed using ggmap package in R to interface with Google Maps application program interface (API). This analysis estimates the travel time from the centroids of each suburbs to five potential MSU hubs [Royal Prince Alfred/RPA, Prince of Wales/POW, Royal North Shore/RNS, Liverpool/LH and Westmead/WH] and 8 thrombolysis capable hospitals. It is proposed that the MSU should be deployed to the cover the suburbs not well covered by thrombolysis and ECR capable hospitals. This step was performed by assigning membership to hospitals within 30 minutes traveling time. The base hub of the MSU was proposed as the closest hub to the least well served suburbs. The population serviceable by MSU was estimated using stroke incidence studies in Melbourne and Adelaide. Results: The largest population serviceable by MSU within 30 minutes (4606 cases), 45 minutes radius (8918 cases) and 60 minutes (10084 cases) was RNS follow by RPA, LPH, WH and POW. POW has the smallest catchment within 30 minutes (3078 cases), 45 minutes (7721 cases) and 60 minutes (9984 cases). Suburbs at the edge of metropolitan Sydney such as the Northern Suburbs are less well served by thrombolysis and ECR capable hospitals. There are 10 suburbs within 30 minutes travel of one hospital. The remainders are within 30 minutes of 2 or more hospitals. Conclusions: Any of the ECR capable hospital can serve as a hub for MSU. We provide a method to identify the hub based on location of suburbs less well served by other hospital.